The Effects of Exposure to Information About Animal Welfare Reforms on Animal Farming Opposition: A Randomized Experiment. (2nd November 2022) - Harris, Jamie; Ladak, Ali; Mathur, Maya B.
ABSTRACT: There is limited research on the effects of animal welfare reforms, such as transitions from caged to cage-free eggs, on attitudes toward animal farming. This preregistered, randomized experiment ( n = 1, 520) found that participants provided with information about current animal farming practices had somewhat higher animal farming opposition (AFO) than participants provided with information about an unrelated topic ( d = 0.17). However, participants provided with information about animal welfare reforms did not report significantly different AFO from either the current-farming ( d = −0.07) or control groups ( d = 0.10). Although these latter effects on AFO were small and nonsignificant, they appeared to be mediated by changes in perceived social attitudes toward farmed animals and optimism about further reforms to factory farming. Exploratory analysis found no evidence that hierarchical meat-eating justification or beliefs about how well-treated farmed animals currently are mediated the effect. Further research is needed to better understand why providing information about animal welfare reforms did not substantially increase AFO overall, whereas providing information about current practice did somewhat increase AFO.